Effect Of The Vertical And Horizontal Web Reinforcement On Deep Beam With Strut-And-Tie Model With Finite Element Analysis - Make, Chee Fong (Universiti Sains Malaysia, 2018)
The research was carried out to study the shear structural behaviour of reinforced concrete deep beams with different ratio of vertical and horizontal web reinforcement. The main objectives of the research are to study the effect of vertical and horizontal web reinforcement on load-deflection response, and stress distribution of deep beam with shear span to depth ratio of 1.67 when subjected to two-point loading. Due to limited research numerical approach, the research was conducted in linear deformation analysis which the material did not go beyond its yield point, the plastic deformation that structure undergo geometric non-linearity deformation will not be considered in this study. The study was conducted by validating the finite element modelling with experimental results. A total of five (5) beams including one control beam with compressive strength of 85MPa with dimension of 1800mm length, 100mm width and 400mm depth, with 550mm of shear span and 330mm of effective depth giving shear span to depth ratio of 1.67 were modelled as simply supported beams in three-dimensional (3D) analysis by finite element analysis (FEA) software, ANSYS 18.2. In the research, reinforcement used was 6T16 for bottom bar, 2T12 for top bar, T8 as vertical web reinforcement bar or shear link and T6 as horizontal web reinforcement bar or midbar. By comparing with beam without any web reinforcement, the beam with 0.56% and 1.26% of vertical web reinforcement caused reduction of 7.43% and 15.60% of mid-span deflection. Among beam with 0.22% horizontal reinforcement, the 1.26% of vertical web reinforcement caused reduction of 11.33% of mid-span deflection compared to beam with 0% vertical web reinforcement. Among beams of vertical reinforcement of 0.56%, and 1.26%, 0.22% of horizontal reinforcement ratio caused 0.11% and 2.93% reduction in mid-span deflection respectively compared to beam with horizontal web reinforcement. Compared to control beam, 0.56% and 0.22% of combined vertical and horizontal web reinforcement caused 7.53% reduction in mid-span deflection, and 1.26% and 0.22% of combined vertical and horizontal web reinforcement caused 18.01% reduction in mid-span deflection. There is good agreement on FEA beam modelled by ANSYS 18.2 with the experimental results in load-deflection response and stress distribution in deep beam when subjected to loading.